A Review on Through-Wall Communications: Wall Characterization, Applications, Technologies, and Prospects - Hojjat Jamshidi-Zarmehri; Amir Akbari; Mohammad Labadlia; Kam Eucharist Kedze; Jafar Shaker; Gaozhi Xiao; Rony E. Amaya (IEEE Access, 2023)
This paper underscores the paramount significance of through-wall communications by providing a comprehensive exploration of pivotal aspects like wall characterization, relevant technologies, versatile applications, and future prospects. Through-wall communication has the potential of being adopted in diverse fields, from indoor wireless communications, ground penetrating radar, through-wall radar imaging, to even power transmission. To augment the efficiency and reliability of signal detection, a whole variety of tools, such as antenna elements, frequency-selective structures, metasurfaces, and lenses, are exploited. By surveying the landscape of relevant technologies and applications in the existing literature, this paper serves as a beacon for researchers and engineers alike. Furthermore, it extends an invitation for pioneering exploration in this field, advocating the examination of tunable and adaptive systems, as well as the untapped potential of 3D printing in reshaping the future of through-wall communications.